Troublesome words - Bryson, Bill (Penguin, 2002)
A clear, concise and entertaining guide to the problems of English usage and spelling that has been an indispensable companion to those who work with the written word. So if you want to discover whether you should care about split infinitives or are cursed with an uncontrollable outbreak of commas, this is the place to find out.